CIP2030 Strategy - International Potato Center (2024)
In a fast-evolving global landscape, CIP2030 is a living, adaptive strategy —our plan for engaging with the present and future challenges facing the world’s agrifood systems. We have listened to our stakeholders and constituencies around the world. We have analyzed external signals and shifts that foreshadow the likely future of agrifood systems; and have evaluated CIP’s internal strengths and weaknesses for adapting to this future. CIP2030 is taking a foresighted approach to set CIP on a path for continuous, critical engagement with global issues and for strengthening our resilience. Achievements from over fifty years of CIP research in potato, sweetpotato and Andean root and tuber crops provide a strong foundation of science capabilities, partnerships, technologies and evidence. Together with our partners we have improved the lives of millions of people in Africa, Asia and Latin America, and together we will adapt and innovate to take on the even greater challenges and opportunities that lie ahead. Root and Tuber Crops are central pillars of future food security in the Global South. As a result of climate change and socio-economic development, their importance will only increase in the decades ahead. CIP and other science and innovation partners have a key responsibility to ensure that root and tuber crops can step up and make much greater contributions. Advanced science tools and innovation capacities are at our disposal to accelerate genetic gain and support sustainable and equitable growth of agrifood systems. The only major food crops not included in ‘Green Revolution’ investments of the past, root and tuber crops can now utilize these science advancements. CIP will work with our current and new partners to bring about a ‘Second Revolution’ that accelerates progress across potato, sweetpotato, cassava, yam, Andean Roots and Tubers, and many other root and tuber crops that are important in different regions of the world. Executive Summary